Pre-breakdown streamer propagation and lightning performance of palm oil with consideration of pressboard and aluminium oxide - Thien, Yee Von (2020)
In recent years, various types of vegetable oils have been introduced as alternatives for Mineral Oil (MO) due to its biodegradability, environmentally friendly, and high flash/fire safety. Palm Oil (PO) has been found as a viable option to be considered as dielectric insulating fluids in transformers. Currently, only some information can be obtained related to the pre-breakdown streamer propagation and lightning performances of vegetable oils such as natural ester i.e. rape seed based. However, there is no information on pre-breakdown streamer propagation for PO either under positive or negative polarities. In addition, the knowledge on the impact of the pressboard on the streamer propagation of the PO is still not available. Furthermore, the effect of the insulative nanoparticles on the lightning properties of the PO has not been examined in previous studies. The aim of this study is to investigate the pre-breakdown and breakdown performances of 2 types of refined, bleached, and deodorized palm oil olein. The streamer propagation and breakdown event in PO either with or without pressboard interface were investigated under both positive and negative lightning voltages. The influence of nanoparticle namely Aluminium Oxide, Al2O3 on the lightning performance of the PO was also considered with and without surfactant. The type of surfactant used in the study was Cetyl Trimethyl Ammonium Bromide (CTAB). MO was also examined for comparison purposes. The lightning impulse voltage tests for all studies were carried out under the needle-plane electrodes configuration at a gap distance of 25 mm based on the rising voltage method. A high-speed camera was used to obtain the streamer propagation with and without pressboard interface while the photomultiplier tube was used to detect the weak emitting light signal in the presence of Al2O3 and CTAB. It is found that the positive lightning performances i.e. streamer propagation and breakdown of both PO are comparable with MO. However, due to different chemical structures, the negative streamers of the PO have more branches and propagate faster than MO. These phenomena lead to the lower negative lightning breakdown voltage of the PO as compared to MO. The positive and negative lightning breakdown voltages for both PO impregnated pressboards are slightly higher than open oil gaps. At the same voltage level, streamers on PO impregnated pressboards propagate further and have lower lightning breakdown voltage than MO impregnated pressboard. After subjected to ageing, the lightning breakdown voltage for both PO and MO impregnated pressboard decrease under both positive and negative polarities. The introduction of Al2O3 can improve the positive lightning breakdown voltages of PO and MO at certain volume concentrations. In addition, the effects of Al2O3 and CTAB on the positive streamer propagation of PO and MO are quite small based on light signal analyses. CTAB can provide a slight further improvement in the positive lightning breakdown voltage at 0.001% concentration Al2O3 for both PO. However, it is apparent that the light signals of all samples increase as the applied voltage increases for both PO and MO.